Electricity Consumption and Industrial Outputs in Economic Community of West African States Countries: Evidence from a Panel Dynamic Ordinary Least Squares and Granger Causality - Aderemi, Timothy A.; Sikwela, Misery M. (International Journal of Energy Economics and Policy, 2025)
This study examines the influence of electricity consumption on industrial outputs in ECOWAS countries from the year 2000 to 2023. The study uses Panel Dynamic Ordinary Least Square regression analysis to obtain long run estimates among the variables, it also uses a Granger-Causality test (to determine the causal relationship between electricity consumption and industrial output). Based on the estimated results, this study concludes the following; electricity consumption contributed a significant positive impact on industrial output in ECOWAS sub region. Similarly, labour force caused a positive and significant impact on industrial output. Whereas, a negative and significant impact of money supply was felt on industrial output in ECOWAS sub region. A uni-directional causality flowing from electricity consumption to industrial output occurred in ECOWAS sub region Due to the findings that emerged from this study, this study recommended that the policymakers in ECOWAS countries should embark on policies that would increase supply and accessibility of electricity to industrial sub sector in all ECOWAS countries in order to ensure a substantial growth in the industrial output of the sub regional economy. In the same vein, the policymakers in ECOWAS sub region could also drive industrial expansion by granting immediate tax relief for privately generated electricity for industrial consumption.